The German Days of Dora Pejačević - Domagoj Marić (Arti Musices)
Dražđani and Monakovo, older Croatian names for Dresden and Munich, were important stops on Dora Pejačević’s life path. Excluding shorter trips that are difficult to trace, e.g. during the First World War, Dora Pejačević stayed in Germany on two occasions – the first time from March 1909 (?) to March 1913, and the second time from the autumn of 1921 until her death in March 1923. On both occasions, Pejačević lived in both cities: on the first occasion, she attended composition classes with composers who are largely forgotten today, Percy Sherwood and Walter Courvoisier. The second occasion was due to her permanent move immediately after her marriage to the Austrian nobleman Ottomar von Lumbe. There is a whole series of questions about the time that Dora Pejačević spent in Germany – in the first place, why did she choose those two German cities, and not, for example, Vienna, Budapest, or Prague? (The question primarily refers to Dresden, since Munich was still a bigger musical centre. After all, in the same period as Dora Pejačević, the Croatian composer Krsto Odak studied in Munich, but there are no known contacts between them.) On both occasions, Pejačević achieved more significant success in Dresden. This is where the publisher Heinrich Bock published at least seven of her works (Op. 18, 19, 20, 22, 23, 24, and 25). On 10 February 1920, before her second move to Germany, her Symphony, Op. 41 was performed in its entirety in Dresden for the first time. In addition to private lessons with Percy Sherwood, Pejačević’s first stay in Dresden was marked by cooperation with Trio Bachmann, with whom she went on tour in October and November 1910 to Budapest, Pécs, Osijek, and Zagreb. Finally, Germany was not only Pejačević’s second homeland but also the first place of her burial, from where her body was transferred to Našice, Croatia, three months after her death. In Našice Dora Pejačević found her final resting place.